Kesejahteraan Psikologis (Psychological Well-Being) pada KSR PMI Kota Surakarta Dalam Menangani Bencana - Rahmawati, Annisaa Nur; , Dr. Moordiningsih M.Si., Psi (2017)
This study aims to understand and describe the psychological well-being of the PMI Surakarta in dealing with the disaster. Informants in this study have characteristics that are a) Become a member of KSR PMI at least 1 year and b) Never handle disaster. Informants in this study amounted to 50 people consisting of KSR PMI Unit Headquarters and Unit UNS. This research uses open questionnaire method. The result of the research shows that KSR PMI Surakarta has high psychological well-being. In general, the KSR PMI members are happy with their peer partner KSR PMI because they can socialize with different individuals. The life goals of KSR PMI also want to benefit others, so that PMI KSR members feel more positive than positive affects